Implementation of an Epidural Rounding Reminder in the Electronic Medical Record Improves Performance of Standardized Patient Assessments during Labor - Ende, Holly B.; French, Benjamin; Shi, Yaping; Damron, James; Bauchat, Jeanette R.; Dumas, Susan; Wanderer, Jonathan P. (Applied Clinical Informatics, 2023)
Background Poorly functioning labor epidural catheters lead to pain and dissatisfaction. Regular catheter assessment ensures timely identification of malfunction and may improve safety by facilitating rapid and successful conversion to general anesthesia for emergency cesarean. Informatics-based systems encourage standardization of care to identify epidural malfunctions earlier.Objectives This article demonstrates that visual epidural rounding reminder display on an electronic patient board would alert clinicians to elapsed time and decrease mean time between assessments.Methods As a quality initiative, we implemented an epidural rounding reminder on our obstetric patient board. The reminder indicated the number of elapsed minutes since placement or last patient assessment. We retrospectively reviewed labor epidural charts 3 months prior to and 5 months following reminder implementation, with a 4-week washout period. The primary outcome was mean time between documented epidural assessments, with secondary outcomes including maximum time between assessments, total number of assessments during labor, catheter replacement rates, and patient satisfaction. Unadjusted comparisons between pre- and postimplementation groups were conducted using Wilcoxon's rank-sum and Pearson's chi-square tests, as appropriate. A test for equal variances was conducted for time between assessment outcomes.Results Following implementation, mean time between assessments decreased from a median of 173 (interquartile range [IQR]: 53, 314) to 100 (IQR: 74, 125) minutes (p <0.001), and maximum time between assessments decreased from median 330 (IQR: 60, 542) to 162 (IQR: 125, 212) minutes (p < 0.001). Total number of evaluations during labor increased from 3 (IQR: 2, 4) to 5 (IQR: 3, 7; p < 0.001). Decreased variance in mean and maximum time between assessments was noted following reminder implementation (p < 0.001). Epidural replacement rates decreased from 14 to 5% postimplementation (p < 0.001). Patient satisfaction was unchanged.Conclusion Implementation of an informatics-based solution can promote standardization of care. A simple epidural rounding reminder prompted clinicians to perform more frequent labor epidural assessments. In the future, these process improvements must be linked to improvements in patient experiences and outcomes.
Keywords: anesthesiology; epidural; labor analgesia; neuraxial analgesia; obstetrics/gynecology